2000
DOI: 10.4049/jimmunol.164.7.3919
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Nonobese Diabetic Mice from Diabetes by Gene(s) Closely Linked to IFN-γ Receptor Loci

Abstract: Nonobese diabetic (NOD) mice carrying a segment of chromosome flanking the disrupted IFN-γ receptor gene from original 129 ES cells are resistant to development of diabetes. However, extended backcrossing of this mouse line to the NOD mouse resulted in a segregation of the IFN-γR-deficient genotype from the diabetes-resistant phenotype. These results indicate that the protection of NOD mice from the development of diabetes is not directly linked to the defective IFN-γ receptor gene but, rather, is influenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
80
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 24 publications
7
80
0
1
Order By: Relevance
“…Furthermore, the few (three) NOD.IFN-␥RB Tg females that did not previously succumb to AMM all developed T1D. These results add to the growing list of evidence (11,(22)(23) that Th1 responses are not essential to the development of T cell-mediated autoimmune T1D in NOD mice. More importantly, our current results indicate that in addition to their inability to inhibit T1D, some protocols which suppress Th1 responses in NOD mice can actually enhance other, normally less pronounced, autoimmune pathologies present in this strain.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, the few (three) NOD.IFN-␥RB Tg females that did not previously succumb to AMM all developed T1D. These results add to the growing list of evidence (11,(22)(23) that Th1 responses are not essential to the development of T cell-mediated autoimmune T1D in NOD mice. More importantly, our current results indicate that in addition to their inability to inhibit T1D, some protocols which suppress Th1 responses in NOD mice can actually enhance other, normally less pronounced, autoimmune pathologies present in this strain.…”
Section: Discussionsupporting
confidence: 53%
“…Indeed, TH2 cells have been reported to transfer diabetes into NOD mice, but only if these animals are immunocompromised (5). The bulk of evidence implicates a TH1-driven type of immunopathology as the dominant force in the development of IDDM (14)(15)(16)(17)(18)(19)(20)(21)(22)(23), arguing that the lack of IL-4R␣ does not mediate its effect by diminishing TH2 effector functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, a targeted mutation in the IFN-␥ gene has been reported to delay but not prevent the onset of diabetes in NOD mice (16). Although IFN-␥R knockout NOD mice were reported to be protected from diabetes (17), more recent work has demonstrated such an effect only in cyclophosphamide-induced acceleration of diabetes; a second gene, linked to the IFN-␥R, plays a role in the resistance originally noted (18). On the other hand, treatment of NOD mice with IL-4 protects against the development of diabetes (6), and transgenic NOD mice expressing IL-4 under the rat insulin promoter are protected (19).…”
mentioning
confidence: 99%
“…In vivo, we have shown that ␤-cells unresponsive to IFN-␥ are protected from destruction in the lymphocytic choriomeningitis virus-induced transgenic mouse model of diabetes (12). On the other hand, we have described that IFN-␥ is a key regulator of class I MHC expression but is not required for ␤-cell destruction in the nonobese diabetic (NOD) mouse model (13,14). TNF-␣ and IL-1 may also be important in ␤-cell damage, although their precise roles remain inconclusive.…”
mentioning
confidence: 96%